HOW SIMULATION-BASED MEDICAL EDUCATION CAN BE STARTED IN LOW RESOURCE SETTINGS - Riaz, Salman (Journal of Ayub Medical College Abbottabad, 2019)
Patient safety and improved healthcare is a major concern for healthcare providers, medical professionals and academic institutions. After the research identified that many patients die because of human error, medical simulation has been increasingly used in developed countries to train medical undergraduates and practitioners. However, most of the developing countries are unable to get benefits from it due to low income and low resource situations. As building simulation centres with high fidelity manikins require modern and expensive equipment, simulated patients and part-task trainers could provide a starting point in developing countries. These are low cost options for developing technical and non-technical skills and very effective for teaching basic concepts to novices. More advanced simulation centres can be established by fund raising with the help of charity organizations at the later stage. Keywords: Medical simulation; Patient safety; Low resource; Standardised Patients